1975
DOI: 10.2134/jeq1975.00472425000400020008x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Reduction and Nitrite Utilization by Nitrifiers in an Unsaturated Hanford Sandy Loam

Abstract: In order to discern any relationship between added nitrate and microbial growth in a field plot, a Hanford sandy loam was infiltrated for 5 weeks at a rate of 5 cm day−1 with a solution containing 100 ppm ‐N and 1.25 meq/liter Cl− as KNO3 and CaCl2 respectively. Nitrate‐N, NO2−‐N and Cl− concentrations in soil solution were determined and corresponding counts of nitrate reducers, denitrifiers, and NH4+‐ and NO2−‐oxidizer populations were made.Ratios of measured to applied concentrations for both NO3−‐N and Cl−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…MacFarlane and Herbert [12] indicated that an additional source of NO 2 may be derived from the dissimilatory reduction of NO 3 to NO2, and that this supported larger populations of NO 2 oxidising bacteria within the sediments. These conclusions are in agreement with those of Voltz et al [13] and Belser [14] who reported that NO 3-dissimilation to NO 2 supported large populations of NO 2 oxidising bacteria in some soils. The reduction or absence of NO 2 oxidising bacteria in the 4-5 cm horizons of marine and estuarine sediments is probably due to their greater sensitivity to reduced concentrations of dissolved 0 2 [15].…”
Section: Data Presented Insupporting
confidence: 93%
“…MacFarlane and Herbert [12] indicated that an additional source of NO 2 may be derived from the dissimilatory reduction of NO 3 to NO2, and that this supported larger populations of NO 2 oxidising bacteria within the sediments. These conclusions are in agreement with those of Voltz et al [13] and Belser [14] who reported that NO 3-dissimilation to NO 2 supported large populations of NO 2 oxidising bacteria in some soils. The reduction or absence of NO 2 oxidising bacteria in the 4-5 cm horizons of marine and estuarine sediments is probably due to their greater sensitivity to reduced concentrations of dissolved 0 2 [15].…”
Section: Data Presented Insupporting
confidence: 93%
“…However, some evidence indicates that nitrite produced from nitrate reduction may be available for the growth of nitrite oxidizers (8,85). In this theory nitrate is reduced to nitrite in anaerobic microenvironments.…”
Section: Substrates and Products Of Ni Trificationmentioning
confidence: 99%
“…Volz et al (1975b) perfused a lysimeter containing a sandy loam soil low in organic matter «0.5 % carbon) with a nitrate solution and observed a peak nitrite concentration in the top 60 cm that corresponded to a low nitrate concentration. They showed that nitrate was first reduced to nitrite by nitratereducing bacteria, and the nitrite was subsequently reoxidized by nitriteoxidizing bacteria as it moved below the nitrite zone.…”
Section: Substrates and Productsmentioning
confidence: 99%